Bukhara During the Political Realities After the Death of Amir Timur (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, Sahibgiron Amir Temur created a huge kingdom during his reign and tried to develop Movarounnah as the core of its central region in every way. The fact that he tried to turn it into the second city after Samarkand, the role of the Bukhara oasis in the struggle for the title among the Timurids was discussed.